Trust building strategies for virtual leaders in the post pandemic era - Badrinarayanan, Vidya (2024)
The coronavirus pandemic has sent an important message that future project teams need to be trained to work under virtual conditions, which has already become the new norm in organizations across the world. As organizations increasingly rely on virtual teams to achieve project objectives, it is essential to comprehend how leadership functions in virtual project teams. The purpose of this research is to analyze the leadership strategies used by project managers for building trust in virtual project teams. This convergent parallel mixed method research was conducted by surveying 185 virtual leaders and conducting a semi-structured interview with 13 senior virtual leaders involved in managing projects across the industry sectors. The research findings indicate that establishing trust was ranked as significant challenges in leading virtual project teams in the post-pandemic era. Additionally, the research findings recommend that virtual leaders need to strive to build a high-trust environment to improve the effectiveness of virtual project teams. As the project management profession struggles with low project success rates, mixed-method research aims to contribute to the knowledge in the growing research area of virtual project leadership. This research contributes to the knowledge by offering first-person accounts from senior virtual leaders on the innovative strategies they had implemented for building trust in the virtual project when there were limited opportunities for face-to-face interaction on account of the pandemic.